Rights of Non-Muslims in the Middle East - Salamey, Imad (2017)
The early centuries of Islam were characterized—in theory and often in practice—by the relatively enlightened treatment of major religious minorities, a practice later institutionalized in large multiethnic, multiconfessional empires under Muslim rule. Yet, developments in the modern Muslim world have failed to keep pace with contemporary understandings of minority rights and freedom of worship. Today, non-Muslims across the Middle East are subject to political, economic, and social discrimination, as well as the very real dangers of outright repression and violence. This phenomenon is driven by both the predominant emphasis on conservative readings of religious law and events on the ground as well as social tensions released by the so-called Arab Spring protests. Together, limitations on political and social expression under the region’s many autocrats, who have been wary of alienating the majority of Muslims, as well as widespread acceptance of restrictive readings of sharia law, have made the notion of equality between Muslims and non-Muslims a distant prospect at best.